Biomarkers and clinical presentations in Creutzfeldt‐Jakob Disease. (20th December 2022) - Shir, Dror; Lazar, Evelyn; Graff‐Radford, Jonathan; Aksamit, Allen; Cutsforth‐Gregory, Jeremy; Jones, David T.; Botha, Hugo; Ramanan, Vijay K; Prusinski, Christian C; Porter, Amanda; Day, Gregory S
Abstract: Background: The ability to detect malformed prion proteins using real‐time quaking‐induced conversion (RT‐QuIC) assays has transformed the diagnostic approach to sporadic Creutzfeldt‐Jakob disease (CJD), facilitating earlier recognition of affected patients. Recognizing this, we evaluated the frequency of clinical features and biomarker results at initial evaluation in patients with CJD and determined the relationship between these early features and CJD diagnosis and prognosis. Method: Clinical data were extracted from the electronic medical records of patients with probable or definite (pathologically confirmed) CJD assessed at Mayo Clinic from 2014‐2021. Diagnoses of probable CJD were established by clinical consensus, referencing the Centers for Disease Control and Prevention diagnostic criteria. Clinical features and biomarkers results were evaluated at presentation, and associations with CJD diagnosis and symptomatic disease duration determined. Result: One‐hundred fifteen patients were included (40, [35%] with definite CJD). Mean age‐at‐symptom onset was 64.8±9.4 years; 68 patients were female (59%). The sensitivity of clinical markers (myoclonus) and tests historically considered in patients with suspected CJD (e.g., stereotyped EEG abnormalities (16%), CSF 14‐3‐3 (60%)) was poor. Biomarkers with good diagnostic sensitivity included RT‐QuIC (93%), t‐tau levels >1149 pg/mL (88%), and characteristic signal abnormalities on MRI (77%). Multivariable linear regression confirmed shorter survival for patients with myoclonus (125.9 days, 95%CI 23.3‐15.5, p=0.026), visual/cerebellar signs (180.19 days, 95%CI 282.2‐78.2, p<0.001), positive 14‐3‐3 (193 days, 95%CI 304.9‐82.9; p<0.001), and elevated t‐tau levels (each 1000 pg/ml increase was associated with a nine‐day shorter time‐to‐death, 95%CI 1‐18; p=0.041). Conclusion: CSF RT‐QuIC and elevated t‐tau levels, and stereotyped MRI abnormalities continue to be strongly associated with the diagnosis in the modern era, while other clinical findings (myoclonus) and biomarkers results traditionally ascribed to CJD (e.g., PSWC on EEG, 14‐3‐3) offered less value in the diagnostic evaluation. Detection of visual or cerebellar features, myoclonus, CSF 14‐3‐3, and t‐tau levels may predict disease duration, justifying inclusion in the evaluation of CJD‐suspected patients.